Studi Fenomenologi Konsep Sehat Sakit Keluarga denga Demam Berdarah Dengue di Kota Padang - Jhunesti Pratiwi; Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2014)
Dengue fever is a disease caused by a virus that can cause dangerous because the patient died Whitin a very short time, which is transmitted by the mosquito Aedes Aegypty. Family experience who success treating patients with dengue fever in the shock phase is very important for the family to be a lesson. Purpose of this study is to explore, understand, and give meaning to the concept of a healthy experience in caring for family members who were suffering from dengue fever. This research is a qualitative descriptive with phenomenological approach with three informants in Padang city in 2013.The results of this study found that families who successfully treated patients with dengue fever until recover have good management practices and they follow the advice of medical personnel to prevent misconduct in taking care of patients. Families need to get an explanation from medical officers in order to take good and right action so the death rate from dengue fever can be avoided.